Kye

## Answered question

2021-02-23

Solve differential equation $\frac{dy}{dx}+y\mathrm{cos}\left(x\right)=4\mathrm{cos}\left(x\right)$, y(0)=6

### Answer & Explanation

Alannej

Skilled2021-02-24Added 104 answers

$\frac{dy}{dx}+y\mathrm{cos}x=4\mathrm{cos}x$
That is $\frac{dy}{dx}+\left(\mathrm{cos}x\right)y=4\mathrm{cos}x$
$\frac{dy}{dx}+P\left(x\right)=Q\left(x\right)$
So $P\left(x\right)=\mathrm{cos}x$, $Q\left(x\right)=4\mathrm{cos}x$
Integrating factor is
$I.F.={e}^{\left(\int P\left(x\right)dx\right)}$
$={e}^{\int \mathrm{cos}xdx}$
$={e}^{\mathrm{sin}x}$
$y\cdot I.F.=\int Q\left(x\right)\cdot I.F.dx+c$
$y{e}^{\mathrm{sin}x}=\int 4\mathrm{cos}x{e}^{\mathrm{sin}x}dx+c$
$=4\int {e}^{\mathrm{sin}x}\mathrm{cos}xdx+c$
$=4\int {e}^{t}dt+c$ (by subtitution)
$=4{e}^{t}+c$
$y{e}^{\mathrm{sin}x}=4{e}^{\mathrm{sin}x}+c$
$y\left(x\right)=4{e}^{\mathrm{sin}x}+c$
Now apply the initial condition y(0)=6 in the general solution
$4{e}^{\mathrm{sin}\left(0\right)}+c=6$
$4{e}^{0}+c=6=>4+c=6$
c=6-4=2 Now substitute 2 for c in general solution
Thus,the particular solution is $y\left(x\right)=4{e}^{\mathrm{sin}x}+2$

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?